2013
DOI: 10.1007/s00535-013-0839-5
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factor profiles, drug usage, and prevalence of aspirin-associated gastroduodenal injuries among high-risk cardiovascular Japanese patients: the results from the MAGIC study

Abstract: BackgroundLow-dose aspirin is widely used for the prevention of cardiovascular events. The prevalence of gastroduodenal injuries and the risk factor profile including gastroprotective drug therapy needs to be clarified in Japanese patients taking daily aspirin for cardioprotection.MethodsThis Management of Aspirin-induced Gastro-Intestinal Complications (MAGIC) study was conducted with a prospective nationwide, multicenter, real-world registry of Japanese patients at high-risk of cardiovascular diseases who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 28 publications
1
36
1
Order By: Relevance
“…Comment: LDA treatment is associated with high prevalence and incidence of peptic ulcers [121]. Esomeprazole reduces the occurrence of peptic ulcers in patients taking LDA [122], and esomeprazole was superior to famotidine in preventing upper GI complications related to LDA, clopidogrel, and thrombolytics [123].…”
Section: Commentmentioning
confidence: 99%
“…Comment: LDA treatment is associated with high prevalence and incidence of peptic ulcers [121]. Esomeprazole reduces the occurrence of peptic ulcers in patients taking LDA [122], and esomeprazole was superior to famotidine in preventing upper GI complications related to LDA, clopidogrel, and thrombolytics [123].…”
Section: Commentmentioning
confidence: 99%
“…95 A prospective registry of Japanese patients taking daily aspirin 96 demonstrated that 6.5% of gastroduodenal ulcers and 29.2% of gastro-enteric erosions, respectively, were detected in 1,454 stable outpatients receiving aspirin for cardioprotective purposes. 97 Proton-pump inhibitors (PPI) are effective in prevention of aspirin-induced gastroduodenal injury, 98 but regular use of PPI is recommended only for high-risk patients. 99 Of note, a recent international prospective registry of patients with or at risk of atherothrombosis revealed a lower incidence of serious bleeding events in patients from Japan as compared with other regions of the world.…”
Section: Thrombin Receptor Antagonists and Anticoagulantsmentioning
confidence: 99%
“…We reported the first study that found H. pylori infection as an independent risk factor for upper GI bleeding in LDA users (OR 4.7, 95 % CI 2.0-10.9) [56]. In the MAGIC study, published recently, H. pylori was associated with an increased risk of ulcer in LDA users (OR 1.83, CI 95 % 1.18-2.88, p = 0.0082) [73]. In contrast, a cohort study showed that H. pylori infection may be a protective factor against LDA-induced gastric erosions [74].…”
Section: H Pylori Infectionmentioning
confidence: 99%